The Struggling Nightingales: Determinants of Resilience and Intention to Stay Among Nurses in a Type C Hospital In Gianyar, Bali, Indonesia - Made Ary Puspitasari; Gede Sri Darma; Agung Nova Mahendra (Green Publisher Indonesia, 2024)
Intention to stay in the nursing profession is a complex phenomenon related to hospital operational management. This study aimed to investigate the relationship between various potential determinants in influencing the intention to stay in nurses who work at a type C private hospital in Gianyar, Bali, Indonesia. This research was an questionnaires-based analytical descriptive study, involving nurses (work period more than one year) from all medical units in the hospital. The relationships between determinants were modeled and analyzed using path analysis. In conclusion, age and work experience have a significant negative influence on burnout levels, while the work environment has a significant negative influence on burnout. Additionally, age and work experience have a significant positive influence on job satisfaction, which is mediated by burnout. Furthermore, job satisfaction has a significant positive influence on resilience, which in turn has a significant positive influence on intention to stay.